Temperature and pressure adaptation of a sulfate reducer from the deep subsurface - Fichtel, Katja; Logemann, Jörn; Fichtel, Jörg; Rullkötter, Jürgen; Cypionka, Heribert; Engelen, Bert (Frontiers in Microbiology, 2015)
Microbial life in deep marine subsurface faces increasing temperatures and hydrostatic pressure with depth. In this study, we have examined growth characteristics and temperature-related adaptation of the Desulfovibrio indonesiensis strain P23 to the in situ pressure of 30 MPa. The strain originates from the deep subsurface of the eastern flank of the Juan de Fuca Ridge (IODP Site U1301). The organism was isolated at 20 °C and atmospheric pressure from ~61 °C-warm sediments approximately five meters above the sediment-basement interface. In comparison to standard laboratory conditions (20 °C and 0.1 MPa), faster growth was recorded when incubated at in situ pressure and high temperature (45 °C), while cell filamentation was induced by further compression. The maximum growth temperature shifted from 48°C at atmospheric pressure to 50°C under high-pressure conditions. Complementary cellular lipid analyses revealed a two-step response of membrane viscosity to increasing temperature with an exchange of unsaturated by saturated fatty acids and subsequent change from branched to unbranched alkyl moieties. While temperature had a stronger effect on the degree of fatty acid saturation and restructuring of main phospholipids, pressure mainly affected branching and length of side chains. The simultaneous decrease of temperature and pressure to ambient laboratory conditions allowed the cultivation of our moderately thermophilic strain. This may in turn be one key to a successful isolation of microorganisms from the deep subsurface adapted to high temperature and pressure.